2014
DOI: 10.2183/pjab.90.145
|View full text |Cite
|
Sign up to set email alerts
|

Emerging novel concept of chaperone therapies for protein misfolding diseases

Abstract: Chaperone therapy is a newly developed molecular therapeutic approach to protein misfolding diseases. Among them we found unstable mutant enzyme proteins in a few lysosomal diseases, resulting in rapid intracellular degradation and loss of function. Active-site binding low molecular competitive inhibitors (chemical chaperones) paradoxically stabilized and enhanced the enzyme activity in somatic cells by correction of the misfolding of enzyme protein. They reached the brain through the blood-brain barrier after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 112 publications
0
56
0
1
Order By: Relevance
“…In those LDs for which the mutations in non-catalytic sites lead to improper folding and triggers their degradation, enzyme enhancement therapy is a valuable approach [101, 102]. This strategy uses pharmacological or molecular chaperones that assist enzymes to fold correctly, thus preventing their degradation, and redirecting them to the lysosome [101, 102]. Examples of pharmacological chaperones include Galafold ™ (Migalastat; 1-deoxygalactonojirimycin) clinically approved for Fabry disease in the E.U.…”
Section: Lysosomes and Lysosomal Storage Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…In those LDs for which the mutations in non-catalytic sites lead to improper folding and triggers their degradation, enzyme enhancement therapy is a valuable approach [101, 102]. This strategy uses pharmacological or molecular chaperones that assist enzymes to fold correctly, thus preventing their degradation, and redirecting them to the lysosome [101, 102]. Examples of pharmacological chaperones include Galafold ™ (Migalastat; 1-deoxygalactonojirimycin) clinically approved for Fabry disease in the E.U.…”
Section: Lysosomes and Lysosomal Storage Disordersmentioning
confidence: 99%
“…Recently, molecules that modulate the function of the molecular chaperone, heat-shock protein 70 (Hsp70), have shown promise for treatment of sphingolipidoses [106, 107]. However, identification of such molecules takes large-scale screening efforts and each molecule is generally specific for just that mutation [102]. Another approach of modulating lysosome trafficking utilizes overexpression of the Rab9 cytosolic molecule, which is linked to endosome maturation and lysosome biogenesis, through gene therapy or protein transduction approaches.…”
Section: Lysosomes and Lysosomal Storage Disordersmentioning
confidence: 99%
“…Didelės mutacijos lemia visišką baltymo nebuvimą arba defektinis baltymas yra, bet nėra jo katalizinės funkcijos [32]. Farmakologiniai šeperonai, mažos molekulės ligandai, endoplazminiame tinkle gali sujungti ir stabilizuoti mutavusį baltymą.…”
Section: Molekulinė šEperonų Terapijaunclassified
“…Moreover, it suppresses α-synuclein overexpression neuroblastoma cell lines [2]. Furthermore, it is suggested to be one of chaperone therapies for protein misfolding diseases such as Gaucher disease [4], and for impairment of autophagy-lysosome system occurred in many…”
Section: Role Of Ambroxol Hydrochloridementioning
confidence: 99%
“…These disorders are known to be related to autophagy machinery impairment [1]. Recent studies have reported roles of Ambroxol hydrochloride in treatment of some oxidative stress induced and autophagy mediated diseases such as Parkinson's disease (PD), related synucleinopathies, Dementia, Alzheimer's, Huntington's, Creutzfeldt-Jakob/prion, and Gaucher (GD) diseases [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%